2017
DOI: 10.5539/jgg.v9n2p24
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Freshwater in Shatt Al- Arab River (Southern Iraq)

Abstract: This study uses data from the current rate of population growth, agricultural development and effects of climate change to estimate the future of water demand and the amount of available water in the Shatt Al-Arab River basin. The Shatt Al-Arab River will be facing a freshwater deficit as a result of the decrease of water received from its tributaries. Currently, the river receives freshwater from the Tigris only, as a result to dam construction projects on the tributaries remaining. In 2040, it is expected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results showed that the samples were within the permissible limits according to the standards of the World Health Organization (WHO), Canadian standards and Iraqi standards, which were 0.2, 0.007, 0.01 ppm, respectively whether for drinking, aquaculture or irrigation purposes. These results of this study were agreed with [12][13][14][15][16].…”
Section: Lead Pbsupporting
confidence: 92%
“…The results showed that the samples were within the permissible limits according to the standards of the World Health Organization (WHO), Canadian standards and Iraqi standards, which were 0.2, 0.007, 0.01 ppm, respectively whether for drinking, aquaculture or irrigation purposes. These results of this study were agreed with [12][13][14][15][16].…”
Section: Lead Pbsupporting
confidence: 92%
“…In 2010, the flow of the Shatt Al-Arab River was completely dependent on the flow from the Tigris River only with a mean annual flow of 1.8 × 10 9 m 3 (58 m 3 /s), with a monthly variation limited from 42 to 90 m 3 /s. during October and May respectively (Al-Asadi, 2017 ; Al-Asadi & Abdulzahra, 2019 ). The water flow in the Shatt Al-Arab River is very complex because it is affected by the tidal phenomenon of the Arabian Gulf where the river experiences a tidal cycle of approximately 13 h (Abdullah, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Shatt al-Arab river, around 200 km long, is formed at the confluence of the Euphrates and Tigris rivers in al-Qurnah City in southern Iraq [22]. Currently, the river depends mainly on freshwater flow from the Tigris river [23,24].…”
Section: Study Areasmentioning
confidence: 99%
“…The Shatt al-Arab river, around 200 km long, is formed at the confluence of the Euphrates and Tigris rivers in al-Qurnah City in southern Iraq [22]. Currently, the river depends mainly on freshwater flow from the Tigris river [23,24]. The water flow in the Shatt Al-Arab river is affected by the tidal phenomenon of the Arabian Gulf, which has a semidiurnal pattern [25,26].…”
Section: Study Areasmentioning
confidence: 99%